Introduction and comprehensive theoretical framework of analysis of Smart Plate retrofitted reinforced concrete members (SPRRCs). (June 2021) - Khezrzadeh, Hamed; Noorani, Samad
Abstract: Several reasons result in the need for retrofitting of existing reinforced concrete structures, and extensive effort is devoted to invent and implement different methods for strengthening RC members. One of the leading rehabilitation techniques is attaching FRP strips, but FRP materials' low ductility has caused several issues such as FRP-structure debonding, boundary layer cracking, and brittle behaviour of the strengthened RC members. To overcome these drawbacks, the Smart Plate (SP) which is a ductile retrofitting cover, is proposed for the first time. This cover is formed by embedding Shape Memory Alloy (SMA) wires in an elastomeric substrate. The SMAs exhibit certain properties, including superelasticity, shape memory effect, and temperature-dependent behaviour, while the elastomer can withstand severe stretches. To investigate SP-retrofitted RC beams (SPRRC) characteristics, at first, a computer program has been developed based on the fiber analytical method to analyse the strengthened concrete members. The program is verified against experimental and finite element method (FEM) data for ordinary, FRPRC, SMARC and SPRRCs members. Following verification, the program and FEM are implemented to conduct a comprehensive analysis of the influential parameters affecting the behaviour of SPRRCs including SMA percentage and working temperature. As a result, the SPRRCs show improved stiffness and strength compared to ordinary beams. They also behave in a ductile way contrary to FRP-strengthened beams. The FMA program and the FEM simulations both indicate that the SMA phase transition temperature significantly alters the performance of SPRRCs. Moreover, FMA and FEM outcomes approve that the smart plate is less likely to debond from the strengthened structural member, which is a remarkable advantage. Additionally, a parametric study is conducted, and a characteristic moment–curvature diagram is proposed, which approves the merits of using SP as an alternative retrofitting cover. These advantages are the significant enhancement in moment capacity, yielding moment, ultimate curvature, and ductility.